Analisis Kesiapan Penerapan Kurikulum Merdeka di Madrasah Ibtidaiyah Negeri 1 Lampung Timur - Rosida (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2022)
This study aims to describe the readiness for independent curriculum implementation in Madrasah Ibtidaiyah Negeri 1 Lampung Timur. The independent curriculum is a policy that focuses on developing student potential and avoiding administrative pressure and other policies, to produce better teacher potential. This research uses qualitative methods with data collection techniques in the form of interviews, observation, and documentation. This study shows the readiness of the implementation of the Independent Curriculum at Madrasah Ibtidaiyah Negeri 1 Lampung Timur, which includes learning planning, learning process, and assessment evaluation. There are advantages to the independent curriculum, such as flexibility for teachers in teaching according to the stage of development and the needs of students. However, there are still weaknesses in the teaching system that have not been well planned. In addition, internal factors such as student motivation, attitudes, and interests, as well as external factors such as parental support, madrasah head leadership, madrasah facilities, learning systems, learning methods, and teacher competence are inhibiting factors in the implementation of the independent curriculum. The obstacles faced in implementing the independent curriculum include limited material books, so teachers have to look for additional sources. In addition, teachers also face challenges in adjusting learning methods to the independent curriculum. This research provides an overview of the readiness to implement the independent curriculum at Madrasah Ibtidaiyah Negeri 1 Lampung Timur, focusing on lesson planning, implementation of the learning process, and evaluation. The obstacles faced in implementing the independent curriculum are an important concern in optimizing the implementation of the independent curriculum in the future.